The Effects of Multi-Scale Climate Variability on Biodiversity Patterns of Chinese Evergreen Broad-Leaved Woody Plants: Growth Form Matters - Xu, Yue; Shen, Zehao; Zhang, Jinlong; Zang, Runguo; Jiang, Youxu (Frontiers in Ecology and Evolution, 2021)
Large-scale patterns of species diversity are thought to be linked to contemporary climate variability and Quaternary glacial–interglacial climate change. For plants, growth forms integrate traits related to competition or migration capacity, which determine their abilities to deal with the climate variability they face. Evergreen broad-leaved woody plants (EBWPs) are major components of numerous biomes in the subtropical and tropical regions. Hence, incorporating phylogenetic (temporal) and biogeographic (spatial) approaches, we assessed the relative importance of short- and long-term climate variability for biodiversity patterns of different growth forms (i.e., tree, shrub, liana, and bamboo) in EBWPs. We used a dated phylogeny and the distribution records for 6,265 EBWP species which are naturally occurred in China, and computed the corrected weighted endemism, standardized phylogenetic diversity and net relatedness index for the four growth forms, respectively. Ordinary least squares linear regressions, spatial error simultaneous autoregressive models, partial regression and hierarchical variation partitioning were employed to estimate the explanatory power of contemporary climate variability and climate-change velocity from the Last Glacial Maximum to the present. Our results showed that short- and long-term climate variability play complementary role in the biogeographic patterns of Chinese EBWPs. The former had larger effects, but the legacy effects of past climate changes were also remarkable. There were also differences in the effects of historical and current climate among the four growth forms, which support growth forms as a critical plant trait in predicting vegetation response to climate change. Compared to the glacial- interglacial climate fluctuation, seasonality as a unique feature of mid-latitude monsoon climate played a dominant role in the diversification and distribution of EBWP species at the macroscale. The results indicated that the relative importance of climate variability at different temporal scales may relate to distinct mechanisms. To understand effects of future climate change on species distribution more thoroughly, climate conditions in different time scales should be incorporated.